Novel cross-linked polystyrenes with large space network as tailor-made catalyst supports for sustainable media. (December 2015) - Marrocchi, Assunta; Adriaensens, Peter; Bartollini, Elena; Barkakaty, Balaka; Carleer, Robert; Chen, Jihua; Hensley, Dale K.; Petrucci, Chiara; Tassi, Marco; Vaccaro, Luigi
Graphical abstract: Highlights: Design and synthesis of novel solid catalytic systems specifically developed for sustainable reaction media. Preparation and characterization of novel polystyrene-based gel-type supports and corresponding polystyrene-immobilized-TBD/TEA. Ring opening of phenyl glycidyl ether by thiophenol. Knoevenagel condensation of benzaldehyde with ethyl cyanoacetate. Michael addition of butanethiol to (E)-benzilydene acetone. Abstract: A novel class of polystyrene-based gel-type resins (SPACeR, SP), containing the large 1, 4-bis(4-vinylphenoxy)benzene cross-linker, is introduced; SP-immobilized 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD) and triethylamine (TEA) bases are synthesized and characterized in terms of their structural, thermal and morphological features, and their catalytic efficiency in a series of fundamental chemical transformations under solvent-free conditions is investigated.